VALUATION OF DEBT SECURITIES FOR THE OBJECTIVES OF ACCOUNTING REPORTING IN THE RUSSIAN BANK - E. Samokhina (Publishing House of the State University of Management, 2017)
The article analyzes the model of market risk management with the help of a system of interrelated limits on debt securities, which take into account the risk of standards and statistical data of risk. The work proves the urgency of the problem of market risk management in credit institutions. The author, using the analysis of market risk factors, builds the structure of the securities portfolio of a credit institution for effective management. The conducted research allows the author to conduct an inseparable connection between all banking standards and a portfolio of securities.